MURABAHAH INVESTMENT FINANCING CONTRACT - Kaukab, M. Elfan; Zahrah, Yannuba Asy Syifa; Musfiroh, Mila Fursiana Salma; Efendi, Bahtiar; Khabib, Ainun; Susanti, Susanti (Jurnal 'Ulwan, 2024)
Murabahah investment financing contract is financing for the procurement of equipment, land, premises and transportation to support a business with a minimum period of six months and a maximum of 60 months or five years and the phenomenon in this research is that the investment financing requirements are more complicated than other financing, the time period and amount of customer installments are determined at the beginning in the middle of the financing, the customer is unable to pay the installments. This research aims to determine the implementation of murabahah investment financing contract and SWOT analysis of murabahah investment financing contract at Bank Syariah Indonesia KCP (Branch Office) Purbalingga, Central Java. Type of field research using a qualitative approach. Data collection through interviews and documentation. The sampling technique uses snowball sampling technique. After the data was collected, data validity was tested using source triangulation and then qualitative descriptive analysis and SWOT analysis. The research results show that the implementation of murabahah financing contract is for the procurement of equipment, land, premises and transportation to support the business. Most customers finance the procurement of store. Customers must fulfil the financing requirements, 5C principles well, and the aspects financed must be halal to obtain the financing. The SWOT analysis of financing includes the strength of financing in accordance with sharia principles and avoiding usury and financing margins which are relatively small. Weaknesses include side streaming, decreased ability to repay customers, and fairly complicated requirements. Opportunities make it easier for banks to market financing because of customers' positive views of financing. The threats of murabahah with bil wakalah contracts open loopholes for customers to do side streaming, customers not paying instalments, instalment payments being delayed, customers withdrawing from financing, and customers running away from responsibility.